Freshwater Mangrove: A Novel Urban Ecosystem for an Enhanced Ecosystem Services in Cities - Arlene L. Gonzales; Takuji W. Tsusaka; Oleg Shipin (BIODIVERS - BIOTROP Science Magazine, 2023)
This R and D on ecological engineering using freshwater mangrove addresses a problem of urban wastewater and, at the same time, water pollution and its health concerns, climate change mitigation, as well as typically low aesthetic appearance of cities. The ecotechnology turns the problem of wastewater flowing into lake from adjacent restaurants into solution for many urban challenges including use of nutrient rich water as a fertilizer for mangrove trees in a Novel Urban Ecosystem (NUE).